2016
DOI: 10.1089/tmj.2015.0212
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Heart Rate Measurement Algorithm for Fingertip Recording of Video Signals with Smartphones

Abstract: In conclusion, the overall accuracy of HR and HRV indices of pulse wave analysis, based on video signals of a smartphone, with the developed algorithm was sufficient for preclinical screening applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 20 publications
1
38
0
5
Order By: Relevance
“…The Heartbeats algorithm (Version 20171120) analyses PPG signals recorded by a standard smartphone camera as described elsewhere 10 . The algorithm discriminates between SR and absolute arrhythmia consistent with AF, using a complex non-linear combination analysis comprising beat-to-beat changes of pulse wave time intervals and pulse wave morphology 10 , 11 . Prior to rhythm analysis, the algorithm performs an automatic data quality check by analysing signal-to-noise ratio and accelerometer data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Heartbeats algorithm (Version 20171120) analyses PPG signals recorded by a standard smartphone camera as described elsewhere 10 . The algorithm discriminates between SR and absolute arrhythmia consistent with AF, using a complex non-linear combination analysis comprising beat-to-beat changes of pulse wave time intervals and pulse wave morphology 10 , 11 . Prior to rhythm analysis, the algorithm performs an automatic data quality check by analysing signal-to-noise ratio and accelerometer data.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, medical-grade smartphone apps based on photoplethysmography (PPG) signal analysis constitute a promising, non-invasive and cost-effective option for AF screening. Without the need for additional devices and fully functional on a device that is present around the globe, these PPG-based apps record signals from the patient’s fingertip, solely using the built-in smartphone camera 10 , 11 . As shown in recent trials, the PPG-based apps can differentiate between AF and sinus rhythm (SR) with a sensitivity and specificity of ≥90% 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A training programme on how to perform measurements is integrated in the app as well as aids and feedback tools. Sensitivity and specifity of atrial fibrillation detection compared to the gold standard electrocardiogram were determined in prospective validation studies [31,32]. Participants diagnosed with absolute arrhythmia during the "AF screening" will undergo a validation phase of up to 2 weeks.…”
mentioning
confidence: 99%
“…In Parpinel et al’s study, higher feasibilities and accuracies were found for contact PPG–based apps compared with the noncontact PPG–based ones [53]. Koenig et al [54] found that their algorithm using PPG to assess HR had a consistent accuracy when compared with ECG (correlation index R>.99).…”
Section: Resultsmentioning
confidence: 99%